The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/19322968221133107
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Bias of Comparator Methods in Analytical Performance Assessments Through Recalibration

Abstract: Background: In analytical performance studies, the choice of comparator method plays an important role, as studies have shown that there exist relevant systematic differences (bias) between laboratory analyzers. The feasibility of retrospective recalibration of measurement results through comparison with methods or materials of higher metrological order to minimize bias was therefore assessed. Method: Existing data from performance studies of continuous and blood glucose monitoring systems were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Whereas a factory calibrated CGM device using venous glucose results for their algorithm should use a venous serum glucose measure, such as Yellow Spring Instrument (YSI) as the reference. Of note, Pleus et al 30 showed experimentally that BGM devices have analytical bias exceeding the acceptable levels defined in the Diabetes Laboratory Analysis Guidelines 46 . Pleus et al 30 also reported the analytical bias of the YSI analyser is above the optimal level 30 .…”
Section: Continuous Glucose Monitoring Device Accuracy Landscapementioning
confidence: 99%
See 4 more Smart Citations
“…Whereas a factory calibrated CGM device using venous glucose results for their algorithm should use a venous serum glucose measure, such as Yellow Spring Instrument (YSI) as the reference. Of note, Pleus et al 30 showed experimentally that BGM devices have analytical bias exceeding the acceptable levels defined in the Diabetes Laboratory Analysis Guidelines 46 . Pleus et al 30 also reported the analytical bias of the YSI analyser is above the optimal level 30 .…”
Section: Continuous Glucose Monitoring Device Accuracy Landscapementioning
confidence: 99%
“…Of note, Pleus et al 30 showed experimentally that BGM devices have analytical bias exceeding the acceptable levels defined in the Diabetes Laboratory Analysis Guidelines 46 . Pleus et al 30 also reported the analytical bias of the YSI analyser is above the optimal level 30 . However, by using higher‐order mass spectrometry glucose readings to recalibrate retrospectively, the analytical bias of the YSI analysers and BGM devices reduced to optimal levels 30 .…”
Section: Continuous Glucose Monitoring Device Accuracy Landscapementioning
confidence: 99%
See 3 more Smart Citations